Networking in Ireland's ethnic enterprises : entrepreneurship and opportunity - Desmond, Niamh (Cambridge Scholars, 2010)
"Networking in Ireland's Ethnic Enterprises: Entrepreneurship and Opportunity" gives readers a thorough and up-to-date insight into the networking practices of ethnic entrepreneurs in Ireland. The book provides readers with a theoretical grounding in formal and informal networking and gives a comprehensive insight into research conducted on ethnic entrepreneurship in a number of countries. The book presents a solid grounding in the fundamentals of ethnic entrepreneurship, and gives readers re ...